Bangladesh : constitutional quest for autonomy - Ahmed, Moudud (Dhaka : University Press, 1979)
On political issues in Bangladesh from 1991-2006.
Includes bibliographical references and index.
Keywords: Democracy -- Bangladesh; Bangladesh -- Politics and government -- 1971-; Bangladesh -- Economic conditions; Bangladesh -- Social conditions